Impacts of Conditionality on Consumption: Evidence from the Family Hope Program in Indonesia - Romi Bhakti Hartarto; Philippe LeMay-Boucher (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2024)
Research has shown that the Indonesian Family Hope CCT Program aimed at improving children's health and education of poor households, has had significant impacts. Using different data, we assess whether it changed recipients' behaviour along other metrics. Despite checks and constraints on how transfers can be spent, low-income families can still spend some of their extra cash on frivolous goods, rather than health and education as intended. Our results show that the program leads recipients to mildly decrease their levels of frivolous consumption and increase their share of spending on education (not for health) when compared to non-participants.
Keywords: O10; O12; I22; I24; 330; CCT; Indonesia; Consumption Allocation; Frivolous Good